Three-Dimensional Aerodynamic Optimization of Single-Layer Reticulated Cylindrical Roofs Subjected to Mean Wind Loads - Bingbing San; Chen Xu; Ye Qiu (Advances in Civil Engineering)
This paper presents a procedure to optimize the rise-to-span ratio of single-layer reticulated cylindrical roofs to improve their aerodynamic performance, by coupling the optimization method with computational fluid dynamics (CFD) and finite element analysis (FEA). Four turbulence models (standard k-ε, RNG k-ε, SST k-ω, and RSM) were used to predict the mean wind loads on cylindrical roofs. The simulation results were compared with wind tunnel data, and the RSM turbulence model was employed. The aim of this paper is to determine the best performing rise-to-span ratio of cylindrical roofs based on the gradient algorithm. Two objective functions were considered to minimize the highest mean suction on the roof surface and the maximum response displacement of the single-layer reticulated cylindrical shell subjected to mean wind loads. The results revealed that a cylindrical roof with a rise-to-span ratio (R/S) of 1/6.25 seems to be most effective in attenuating high suctions on the roof surface. In addition, a single-layer reticulated cylindrical shell with R/S = 1/5.5 gives the best performance in reducing the maximum response displacement against wind loads.